Posterior cruciate ligament deficiency: Biomechanical and biological consequences and the outcomes of conservative treatment: A systematic review - Grassmayr, M. J.; Parker, D. A.; Coolican, M. R. J.; Vanwanseele, B. (Journal of Science and Medicine in Sport, 2008)
The objective of the study was to evaluate the biomechanical and biological consequences of posterior cruciate ligament deficiency, determine compensatory mechanisms and assess the efficacy of non-operative treatment. Medline, CINAHL, SPORTdiscus, Cochrane Central Register of Controlled Trials and the Cochrane Database of Systematic Reviews were searched at 30th October 2006 for the terms "PCL" and "posterior cruciate ligament" both independently and including the terms "injury", "deficiency" and "insufficiency". Literature searches identified 598 potentially relevant articles, after exclusions there were 47 articles that fulfilled the inclusion criteria: 30 articles analyzing PCL deficiency and 17 studies on the outcomes for non-operative treatment. The authors reviewed all selected articles and abstracted data into predetermined tables depending upon classification. Studies indicate that posterior cruciate ligament deficiency results in posterior tibial translation with combined injuries displaying greater laxity. Results were inconsistent for rotational stability but deficiency increases joint contact pressure and may result in articular damage. A loss of proprioception occurs but the effect on strength and kinetics is inconclusive. There is a lack of evidence for compensatory muscle activity. Return to activity is possible for the majority of non-operatively treated grade I and II isolated injuries. Comparative analysis was not possible in many instances due to study design or experimental protocols. Further research is required to establish the compensatory mechanisms stabilizing the posterior cruciate ligament deficient knee and to investigate the outcomes for non-operatively treated patients.